Wormhole attack detection in wireless ad hoc networks - Gorlatova, Maria A (University of Ottawa (Canada), 2007)
This thesis deals with wormhole attack discovery in mobile wireless ad hoc networks. Two separate approaches to wormhole attack discovery are developed in this thesis. One approach -- based on protocol-breaking -- allows detection of wormholes that disrupt network operations by dropping network packets. Another -- a novel frequency-based analysis of periodic network messages -- detects wormholes that do not drop traffic. The developed wormhole attack discovery techniques are local, do not rely on specialized hardware or clock synchronization, and do not require modification to existing ad hoc network routing protocols. In addition, tools that are necessary for ad hoc network attack research are created. Network traffic analyzer modules applicable to ad hoc network research are developed and tested. Also, a realistic implementation of a wormhole attack in the NS-2 network simulator is created.
Keywords: Engineering, Electronics and Electrical.